2014
DOI: 10.18632/oncoscience.27
|View full text |Cite
|
Sign up to set email alerts
|

A novel role for the SUMO E3 ligase PIAS1 in cancer metastasis

Abstract: Tumor metastasis contributes to the grave morbidity and mortality of cancer, but the mechanisms underlying tumor cell invasiveness and metastasis remain incompletely understood. Here, we report that expression of the SUMO E3 ligase PIAS1 suppresses TGFβ-induced activation of the matrix metalloproteinase MMP2 in human breast cancer cells. We also find that knockdown of endogenous PIAS1 or inhibition of its SUMO E3 ligase activity stimulates the ability of TGFβ to induce an aggressive phenotype in three-dimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(55 citation statements)
references
References 38 publications
3
52
0
Order By: Relevance
“…PIAS1 is also thought to be a critical regulator in the epithelial mesenchymal transition (EMT) [41]. It has been reported that the expression of PIAS1 regulates the TGFβ-induced metastasis of breast cancer with PIAS1 as a possible biomarker for metastasis in breast cancer [42]. Our data shows that either form of NR causes an up regulation of PIAS1 in the proteomic and gene expression data and SUMOylation in the gene ontology report.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…PIAS1 is also thought to be a critical regulator in the epithelial mesenchymal transition (EMT) [41]. It has been reported that the expression of PIAS1 regulates the TGFβ-induced metastasis of breast cancer with PIAS1 as a possible biomarker for metastasis in breast cancer [42]. Our data shows that either form of NR causes an up regulation of PIAS1 in the proteomic and gene expression data and SUMOylation in the gene ontology report.…”
Section: Discussionsupporting
confidence: 52%
“…A protein is SUMOylated by covalent conjugation of small ubiquitin-like modifier (SUMO) protein, through the use of E1, E2, and E3 ligase enzymes, to lysine residues of the target protein [42],[43]. The function of PIAS1 is as an E3-type SUMO ligase.…”
Section: Discussionmentioning
confidence: 99%
“…For in vivo sumoylation assays, cells were lysed in TNTE (50 mM Tris, 150 mM NaCl, and 1 mM EDTA) buffer containing 0.5% Triton X-100 along with protease and phosphatase inhibitors, and 0.1% SDS. 69,73,76 In addition, 20 mM NEM isopeptidase inhibitor was included in the lysis buffer where indicated. 45,65 Cell extracts were collected in 1.75 ml Eppendorf tubes and centrifuged at 14 000 × g for 10 min at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, SUMOylation and PIAS1 have shown to play a key role in the transcriptional maintenance of basal breast cancer phenotype (Bogachek et al, 2014). Evidence for a role of the PIAS1 in suppression of TGF-b-induced activation of matrix metalloproteinase MMP2 in breast cancer cells has been also reported (Dadakhujaev et al, 2014). However, there is no genomewide information of the role that PIAS1 plays in the regulation of AR target genes in breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%